An Ex-Post Energy Rate Mechanism for Distribution Networks Based on Real Time Metering - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2016)
The integration of generation units into distribution networks has led to a definition for the rates associated with the injections of power, as traditional distribution networks only consider tariffs for energy consumption. Such rate definitions have considered several aspects of the problem (such as the cost of operating the distribution network, the nature of the injections and feed-in tariff), so rates amongst different systems differ, not only because of the different energy prices but also because of different definitions that may not be consistent. This paper proposes a systematic definition for the injection tariff in distribution systems. The definition considers that the distribution system has a given operation cost, and that the tariff must be dynamic to represent the contribution of the injection (negative or positive) to the cost of operating the distribution system. © 2015 IEEE.